Case report: Recreational nitrous oxide abuse triggered peripheral neuropathy possibly through the immune-mediated pathogenesis - Dong, Mei-Xue; Wang, Qing; Xu, Jun-Feng; Hu, Ling; Yu, Ying; Li, Tao (Frontiers in Neurology, 2022)
Nitrous oxide (N2O), commonly known as laughing gas, is widely used in clinical practice and food industry. However, an increasing number of young people have been abusing N2O for recreational purpose, resulting in many functional disorders and sometimes irreversible nerve damage. We present the case of a 20-year-old N2O abuser who gradually developed peripheral neuropathy after continuously inhaling N2O for 2 months. The neurological symptoms of the patient had kept exacerbation for the next 2 months until she came for medical care sitting in a wheelchair. We suggested the patient halting N2O intake and supplementing methylcobalamine according to the standardized protocol. Her symptoms had partly recovered during the following 2 weeks but remained unchanged in another 2 weeks. Antibodies against ganglioside complexes were detected and anti-GM1 IgM antibodies were positive in both cerebrospinal fluid and serum. Intravenous immunoglobulin was given as an additional treatment and the patient's symptoms had significantly recovered further. The patient discharged walking by herself. Then she has been continuously followed up in outpatient department for the next 4 months and taking steroid hormone as well as methylcobalamine. Her symptoms gradually disappeared and all the electrophysiological parameters significantly improved. With this case we were able to show that N2O-related peripheral neuropathy is not only a metabolic disorder but also an immune-mediated disease. N2O intake can trigger a mimic Guillain-Barré syndrome.